Single-Word Predictions of Upcoming Language During Comprehension: Evidence from the Cumulative Semantic Interference Task - Kleinman, Daniel (Cogn Psychol, 2015)
Comprehenders predict upcoming speech and text on the basis of linguistic input. How many predictions do comprehenders make for an upcoming word? If a listener strongly expects to hear the word “sock”, is the word “shirt” partially expected as well, is it actively inhibited, or is it ignored? The present research addressed these questions by measuring the “downstream” effects of prediction on the processing of subsequently presented stimuli using the cumulative semantic interference paradigm. In three experiments, subjects named pictures (sock) that were presented either in isolation or after strongly constraining sentence frames (“After doing his laundry, Mark always seemed to be missing one…”). Naming sock slowed the subsequent naming of the picture shirt – the standard cumulative semantic interference effect. However, although picture naming was much faster after sentence frames, the interference effect was not modulated by the context (bare vs. sentence) in which either picture was presented. According to the only model of cumulative semantic interference that can account for such a pattern of data, this indicates that comprehenders pre-activated and maintained the pre-activation of best sentence completions (sock) but did not maintain the pre-activation of less likely completions (shirt). Thus, comprehenders predicted only the most probable completion for each sentence.